2011
DOI: 10.1007/s10620-011-1637-7
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of the Combination Therapy with Oral and Topical Mesalazine for Patients with the First Episode of Radiation Proctitis

Abstract: The combination of oral and topical mesalazine therapy for radiation proctitis may be a safe and effective treatment for naive radiation proctitis, especially for hemorrhagic proctitis. A large, randomized controlled trial is required to confirm the results of this pilot study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 26 publications
1
15
0
2
Order By: Relevance
“…However, radiotherapy techniques have completely changed since the 70 s, thus the results of the above mentioned trial might not be suitable to present day. One prospective study assessed the efficacy of combined oral and topical mesalazine in 23 patients with chronic PRD, and found that mesalazine significantly improved rectal bleeding, but not other radiation-related symptoms (i.e., pain, tenesmus and stool frequency) after 4 wk of treatment [41] . Current evidence does not support mesalazine routine use for the treatment of acute nor chronic PRD.…”
Section: Aminosalicylatesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, radiotherapy techniques have completely changed since the 70 s, thus the results of the above mentioned trial might not be suitable to present day. One prospective study assessed the efficacy of combined oral and topical mesalazine in 23 patients with chronic PRD, and found that mesalazine significantly improved rectal bleeding, but not other radiation-related symptoms (i.e., pain, tenesmus and stool frequency) after 4 wk of treatment [41] . Current evidence does not support mesalazine routine use for the treatment of acute nor chronic PRD.…”
Section: Aminosalicylatesmentioning
confidence: 99%
“…Current evidence does not support mesalazine routine use for the treatment of acute nor chronic PRD. However, a 4 wk treatment of mesalazine, once daily as a 1 g rectal suspension, might be considered in patients referred for chronic rectal bleeding developed after radiation treatment, as second-line therapy [41] .…”
Section: Aminosalicylatesmentioning
confidence: 99%
“…A recent study on 23 patients with CRP showed a decrease in bleeding with a combination of oral and topical mesalamine [Kochhar et al 1991]. A small, randomized clinical trial showed clinical and endoscopic improvement with a combination of oral sulfasalazine and rectal prednisolone [Seo et al 2011].…”
Section: Discussionmentioning
confidence: 99%
“…Seo et al 28 reported on a trial employing mesalazine, a mainstay of treatment for ulcerative colitis, to treat 23 patients. Three patients required APC for severe bleeding and were excluded from the trial, leaving 20 evaluable patients.…”
Section: Topical Agentsmentioning
confidence: 99%